STRUCTURE OF THE INTRAPLATE EASTERN PALMYRIDE FOLD BELT, SYRIA - Searle, M (1994)
The Palmyride Fold Belt is an aulacogen within the Arabian plate linked to the Levantine continental margin, which contains >10km of Phanerozoic sediments. Recent field mapping shows that almost all the structures have resulted from a phase of northwest-southwest compression followed by major dextral transpression. A regional Palmyride strain ellipse is presented to explain the geometry of structures. There is no evidence for a major basal detachment underlying the Palmyrides. All folding and faulting can be related to disharmonic folding of the Mesozoic sediments above a Triassic evaporite sequence and subsequent dextral transpression. -from Author